PERTANGGUNGJAWABAN PIDANA NAKHODA KAPAL DALAM KECELAKAAN KAPAL MENURUT UNDANG-UNDANG NOMOR 17 TAHUN 2008 TENTANG PELAYARAN - UTAMI, SUTRI; Erdianto, Erdianto; Edorita, Widia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
Marine transportation in the islands countries should be most requested, because there are islands only be connected through maritime transport, but in Indonesia sea tarnsportasi not managed optimally. Various provisions of the International has been ratified even national provisions also complete, but the implementation of these provisions is still limited to business interests and ignoring the security and safety aspects of shipping. In any event the causes of accidents always publicized accident was human error in this case the vessel skipper, but the general human error is always preceded by human error before shipping. In the numerous event of accident during the cruise ships often announced that the number of passengers is not in accordance with manisfest or even a boat called over-load.The writing of this thesis is entitled